Evolution of Individual Preferences and Persistence of Family Rules - Alessandro Cigno; Alessandro Gioffré; Annalisa Luporini (Center for Economic Studies and Ifo Institute (CESifo), 2020)
How does the distribution of individual preferences evolve as a result of marriage between individuals with different preferences? Could a family rule be self-enforcing given individual preferences, and remain such for several generations despite preference evolution? We show that it is in a couple's common interest to obey a rule requiring them to give specified amounts of attention to their elderly parents if the couple's preferences satisfy a certain condition, and the same condition is rationally expected to hold also where their children and respective spouses are concerned. Given uncertainty about who their children will marry, a couple's expectations will reflect the probability distribution of preferences in the next generation. We show that, in any given generation, some couples may obey the rule in question and some may not. It is also possible that a couple will obey the rule, but their descendants will not for a number of generations, and then obey it again. In the long run, if matching is entirely random, either everybody obeys the same rule, or nobody obeys any. If matching is restricted to particular subpopulations identifiable by some visible trait, such as religion or colour of the skin, different subpopulations may obey different rules. The policy implications are briefly discussed.
Keywords: C78; D13; J12; 330; family rule; care of the elderly; matching; evolution; migration